SHBG, free testosterone, and Type 2 Diabetes risk in middle-aged African men: a longitudinal study - Norris, Shane; Seipone, Ikanyeng D.; Mendham, Amy E.; Storbeck, Karl-Heinz; Oestlund, Imken; Kufe, Clement N.; Chikowore, Tinashe; Masemola, Maphoko; Crowther, Nigel J.; Kengne, Andre Pascal; Olsson, Tommy; Brown, Todd; et al. (Oxford University Press, 2024)
Objectives: To investigate longitudinal changes in SHBG and free testosterone (free T) levels among Black middle-aged African men, with and without coexistent HIV, and explore associations with incident dysglycaemia and measures of glucose metabolism. Design: This longitudinal study enrolled 407 Black South African middle-aged men, comprising primarily 322 men living without HIV (MLWOH) and 85 men living with HIV (MLWH), with normal fasting glucose at enrollment. Follow-up assessments were conducted after 3.1 ± 1.5 years. Methods: At baseline and follow-up, SHBG, albumin, and total testosterone were measured and free T was calculated. An oral glucose tolerance test at follow-up determined dysglycaemia (impaired fasting glucose, impaired glucose tolerance, type 2 diabetes) and glucose metabolism parameters including insulin sensitivity (Matsuda index), insulin resistance (homeostasis model assessment of insulin resistance), and beta(β)- cell function (disposition index). The primary analysis focussed on MLWOH, with a subanalysis on MLWH to explore whether associations in MLWOH differed from MLWH. Results: The prevalence of dysglycaemia at follow-up was 17% (n = 55) in MLWOH. Higher baseline SHBG was associated with a lower risk of incident dysglycaemia (odds ratio 0.966; 95% confidence interval 0.945-0.987) and positively associated with insulin sensitivity (β = 0.124, P < .001) and β-cell function (β = 0.194, P = .001) at follow-up. Free T did not predict dysglycaemia. In MLWH, dysglycaemia prevalence at follow-up was 12% (n = 10). Neither baseline SHBG nor free T were associated with incident dysglycaemia and glucose metabolism parameters in MLWH. Conclusion: SHBG levels predict the development of dysglycaemia in middle-aged African men but do not exhibit the same predictive value in MLWH.
Keywords: Free testosterone; Sex hormone-binding globulin; Dysglycaemia; Type 2 diabetes; Africa; SDG-3: Good health and well-being